Effectiveness of Humanistic-Based Group Counselling to Improve Student Well-Being at MAN 1 Medan - Ardiva Morlindah Tripertiwi; Alfin Siregar (MASI Mandiri Edukasi, 2025)
Students are the main subjects in the educational process at school, where Guidance and Counselling (BK) teachers act as facilitators to help students optimise their personal development to become independent, responsible, and prosperous individuals. Student Well-Being can be measured through several indicators, including positive feelings and freedom from anxiety or depression, rational thinking, academic fluency, good social involvement, and the absence of social issues such as isolation. This research aims to: (1) determine the condition of Student Well-Being of MAN 1 Medan students before and after receiving group counselling services with a humanistic approach; and (2) test the effectiveness of group counselling services with a humanistic approach in improving Student Well-Being. Penelitian menggunakan metode kuantitatif dengan jenis pre- The experiment and design used is One Group Pretest-Posttest. The sampling technique used is purposive sampling. The research population consists of 120 students from class XI Science B-1, Science B-2, and Science B-3, with 15 students selected as samples that meet the criteria, namely 13 students in the low Student Well-Being category and two students in the moderate category. The measurement instrument used is a Likert scale. Data analysis was conducted using the non-parametric statistical test Wilcoxon Signed Rank Test, through SPSS version 20. The research results showed an average pretest score of 72.87 and a posttest score of 131.27, indicating an improvement. The hypothesis test obtained an Asymp. Sig value. (2-tailed) of 0.01 (< 0.05), which means there is a significant difference between the pretest and posttest data. Thus, the group guidance services with a humanistic approach have proven effective in improving the Student Well-Being of students at MAN 1 Medan.